Does the modality of measures influence the relationship among working memory, learning and fluid intelligence?. (15th January 2017) - Zeller, Florian; Wang, Tengfei; Reiß, Siegbert; Schweizer, Karl
Abstract: The current study examined the influence of modality on the relationship between learning and fluid intelligence in order to provide an account of disparate research results: on one hand there are results suggesting a moderate relationship between learning and fluid intelligence, whereas on the other hand there are results proposing no such relationship. We applied both figural and verbal measures for tapping learning and fluid intelligence and compared the correlations. Further, working memory, which also was measured by figural and verbal tasks, was included as a common cognitive source and therefore expected to explain the correlation between learning and fluid intelligence. Results showed that there was a substantial correlation between learning and fluid intelligence when the measures showed the same modality. Working memory, showing the same modality, explained this relationship to a larger extent than when working memory showed a different modality. These results suggest that modality has an impact on the relationships between fluid intelligence, learning and working memory. Highlights: Link between verbal learning and Gf was best explained by verbal working memory (WM). Relation between figural learning and Gf was best explained by figural WM. Links between learning and Gf were partly explained by WM with a different modality. Both domain-general and -specific components of WM are crucial for learning and Gf.